Sol-gel coatings with the fluorescence dye Rhodamine B for optical modification of cotton - Wang Yuan; Thomas Grethe; Boris Mahltig (Communications in Development and Assembling of Textile Products, 2023)
The sol-gel method is a versatile tool for the modification and functionalization of textiles. This method can be also used to support the application of dyes on textile materials. This paper is related to the application of the fluorescence dye Rhodamine B together with an industrial sol-gel component. Beside fluorescence spectroscopy, also scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) are used for the investigation of the produced textile samples. The realized fluorescence effects are strongly related to the applied dye concentration and can be drastically enhanced by presence of the applied sol-gel system. By use of sol-gel method also the dry and the wet rubbing fastness can be improved. These results could be the starting point for future development of new fluorescent textile materials.